Effects of traditional strength vs. combined strength and plyometric training on sprint, jump, and maximum strength performance in elite youth soccer players - a 6-month controlled trial - Kadlubowski, B.; Keiner, M.; Wirth, K.; Csapo, R. (The Journal of Strength and Conditioning Research, 2025)
Soccer relies on dynamic movements like sprinting, jumping, and directional changes, with explosive actions crucial for scoring. Despite numerous studies on enhancing speed and jumping ability, the effectiveness of isolated plantar flexor muscle strength training remains unclear. This study compared the effects of combined training interventions—back squats with either calf raises or plyometric training—on sprint, jump, and maximum strength performance in youth soccer players. Over 6 months, 89 male players from 2 elite training centers in Germany were divided into 3 groups: plyometric exercises plus back squats (PLY-BS), calf raises plus back squats (CR-BS), and a control group with conventional soccer-specific training. Outcome measures included back squat and calf raise 1 repetition maxima (1RM), linear sprints (5, 10, 30 m), and countermovement (CMJ) and drop jump (DJ) performance from varying heights. Except for the 5-m sprint and BS 1RM, both intervention groups showed significant improvements compared with the control. Significant "time × group" interactions were found for 10 and 30 m (p < 0.001, 0.181 < n2p < 0.226), CMJ (F(2,81) = 7.089, p < 0.005, n2p = 0.149), and all DJ heights (p < 0.001, 0.190 < n2p < 0.295). Effect sizes for 10, 30 m, and CMJ were similar, but DJ performance showed slightly greater gains in the CR-BS group than in the PLY-BS group. Our findings suggest that combining back squats with calf raises or plyometrics can significantly enhance sprint and jump performance in youth soccer players, with calf raises offering superior improvements in drop jump performance.